Affective judgment in spatial context: How places derive affective meaning from the surroundings. (September 2016) - Blaison, Christophe; Hess, Ursula
Abstract: Why do we favor some places over others? Much is known about the intrinsic properties that make places appear good or bad. The present research investigates the complementary question: How places derive affective meaning from the surroundings. In six experiments we showed how the appraisal of target places changed when the surroundings contained a negatively valenced location. In accordance with a model of affective judgment in spatial context that combines the inclusion/exclusion model of assimilation and contrast and range theory, places were either negatively or positively affected. The specific effect depended on the negatively valenced location's gradient of influence and on the size of the chunk of environment people considered for their judgment. The results fill an important gap in the place appraisal literature. Graphical abstract: Highlights: People's appraisal of places is influenced by other places in the spatial context. Bad locations have negative and positive effects on the surroundings. It depends on people's belief about how far negative influence spreads. It depends on the chunk of spatial context people consider for judgment.